DRAMATURGI KELUARGA PASIEN COVID-19 DAN PERAWAT AMBULAN GAWAT DARURAT SAAT PENJEMPUTAN - Maria Jashinta Elisabet Hamboer (Universitas Prof. Dr. Moestopo (Beragama), 2022)
In the momentum of picking up Covid-19 patients, there was a relatively short communication process in an effort to provide mutual support. Patients' families often experience an ironic phenomenon, on the one hand they must persuade the patient to be willing to be picked up, on the other hand it is impossible to refuse the arrival of an ambulance. On the other hand, AGD nurses are required to have effective impression management skills in motivating patients. The purpose of the study was to find out the dramaturgy of the family of Covid-19 patients and AGD (Emergency Ambulance) nurses at the time of pickup with a qualitative approach with the phenomenological method. The results show that on the family backstage, they convince each other that picking up patients is the most appropriate thing, because covid-19 can be contagious and deadly. On the front stage, they asked nurses to provide guarantees of recovery and information as soon as possible when patients could be visited. As for the backstage of the AGD nurses, they coordinate with each other among the pick-up team members to consistently implement the communication protocol, which contains strategic actions and communicative actions towards patients and their families. Meanwhile, on the front stage, nurses build sympathetic, empathetic and altruistic meanings, that in tackling COVID-19, a coordinating role is needed at all levels of communication.